Differentiating Khmer Stoneware Production: An NAA pilot study from Siem Reap Province, Cambodia. (16th December 2015) - Grave, P.; Stark, M.; Ea, D.; Kealhofer, L.; Tan, B. S.; Tin, T.
Abstract : We report analytical results for stoneware samples from four excavated Angkor‐period kilns in the Greater Angkor area. Previous work has suggested that establishing distinct chemical signatures for kiln complexes in this region is problematic. The current study highlights the effectiveness of neutron activation analysis (NAA) for differentiating the products of Angkorian kiln complexes; it also confirms the viability of a larger‐scale research programme to understand the relationship between Khmer stoneware production and patterns of distribution across the wider Angkorian territory. Evidence of ceramics excavated at kiln sites but produced elsewhere highlights the complexity of consumption patterns during the Angkorian period.